Development of Quantum Simulator for Emerging Nanoelectronics Devices. (28th August 2012) - Hien, Dinh Sy
Abstract : We have developed NEMO-VN2, a new quantum device modeling tool that simulates a wide variety of quantum devices including the resonant tunneling diode, the single electron transistor, the molecular field effect transistor, the carbon nanotube field effect transistor, and the spin field effect transistor. In this work the nonequilibrium Green's function is used to perform a comprehensive study of the emerging nanoelectronics devices. The program has been written by using graphic user interface of Matlab. NEMO-VN2 uses Matlab to solve Schrodinger equation to get current-voltage characteristics of quantum devices. In the paper, we present a short overview of the theoretical methodology using non-equilibrium Green's function for modeling of various quantum devices and typical simulations used to illustrate the capabilities of the NEMO-VN2.